Can Prenatal and Postnatal Cell Phone Exposure Increase Adverse Maternal, Infant and Child Outcomes? - Farzaneh Ashrafinia; Somayeh Moeindarbari; Parisa Razmjouei; Masumeh Ghazanfarpour; Mona Najaf Najafi; Amir Ali Moodi Ghalibaf; Fatemeh Abdi (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To determine the association between maternal mobile phone use and adverse outcomes in infants, children, and mothers. Method In March 202, we conducted a search on the MEDLINE, Embase, and Scopus databases. Data extraction and an assessment of the quality of the studies were performed by two authors. The quality of the studies was assessed using the checklist of the Newcastle-Ottawa scale. Results Studies assessing behavioral problems in infants aged 6 to 18 months reported null findings. However, an increased risk of emotional and behavioral disorders was observed in children aged between 7 and 11 years whose mothers had been exposed to cell phones. The findings regarding the association between maternal cell phone exposure and adverse outcomes in children aged 3 to 5 are controversial. A study found a significant association between the call time (p=0.002) or the history of mobile phone use (in months) and speech disorders in the children (p=0.003). However, another study found that maternal cell phone use during pregnancy was not significantly associated with child psychomotor and mental developments. Inconclusive results were observed about the adverse outcomes in fetuses, such as fetal growth restriction or t scores for birth weight in cell phone users as opposed to non-users. On the contrary, the children ofmothers who were cell phone users had a lower risk of scoring low on motor skills. Similar results were observed regarding the adverse outcomes of cell phone use in infants, such as fetal growth restriction or low birth weight, and the risk of preeclampsia was lower among subjects with medium and high cell phone exposure, as opposed to those with low exposure. Conclusion Studies on behavioral problems have reported different postnatal results, such as null findings among infants and a positive association in children.